Vertical Root Fracture Repair with Resin Composite; Three-Year Follow-up - Ines Kallel; Eya Moussaoui; Nabiha Douki (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
According to the American Association of Endodontists, "a ’true’ vertical root fracture is defined as a complete or incomplete fracture initiated from the root at any level, usually directed buccolingually." Vertical root fracture (VRF) usually starts from an internal dentinal crack and develops over time, due to masticatory forces and occlusal loads. When they occur in teeth, those types of fractures can present difficulties in diagnosis, and there are however many clinic and radiographical signs which can guide clinicians to the existence of the fracture. Prognosis, most often, is hopeless, and differential diagnosis from other etiologies may be difficult sometimes. Patients with VRFs typically present with minimal signs and symptoms during the early stage. In this paper, we present a case of VRF diagnosed after surgical exploration; the enlarged fracture line was filled with a fluid resin. A 36-month clinical and radiological follow-up showed an asymptomatic tooth, reduction of the periodontal probing depth from 7 mm prior to treatment to 4 mm with no signs of ankylosis. In this work, the diagnosis and treatment alternatives of vertical root fracture were discussed through the presented clinical case.